2013
DOI: 10.1179/2045772312y.0000000079
|View full text |Cite
|
Sign up to set email alerts
|

Marfan syndrome and symptomatic sacral cyst: Report of two cases

Abstract: Context: Meningeal abnormalities such as dural ectasia are seen in Marfan syndrome, but spinal meningeal cysts are rarely seen. These cysts usually asymptomatic and often found incidentally on magnetic resonance imaging, large cysts may cause neurological deficits and pain secondary to nerve root compression. Design: Case reports. Findings: Two patients with Marfan syndrome presented with urinary symptoms secondary to dural ectasia and sacral cysts. Patient 1 had a history of low back pain, erectile dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…In the study by Marino, et al, examination of family histories suggested that Tarlov cysts have both vertical and lateral inheritance, in some cases. A report connecting Tarlov cysts with Marfan syndrome supports a genetic hypothesis for some patients [8]. Hydrostatic pressure might also be a contributing factor and potentially the reason the S2 nerve root is so commonly involved [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Marino, et al, examination of family histories suggested that Tarlov cysts have both vertical and lateral inheritance, in some cases. A report connecting Tarlov cysts with Marfan syndrome supports a genetic hypothesis for some patients [8]. Hydrostatic pressure might also be a contributing factor and potentially the reason the S2 nerve root is so commonly involved [9].…”
Section: Discussionmentioning
confidence: 99%
“…24 Many of the Marfan syndrome pathologies related to the spinal meninges, such as dural ectasia, arachnoid cysts, and meningeal cysts, often do not produce any symptoms; however, radicular, myelopathic, and urinary symptoms from such pathologies have been reported in patients with this syndrome. 1,5,14,17,21,23 In addition, spontaneous spinal CSF leaks are much more commonly observed in patients with Marfan syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A direct surgical approach is associated with a high risk of dural tears and osseous complications. 1 The advantage of our approach over other surgical methods is that it is less likely to tear the dura while accomplishing direct obliteration of the connection between the thecal sac and cyst. Other approaches may accomplish the same goal without using an aneurysmal clip, but are more likely to cause dural tearing, especially in patients with Marfan syndrome.…”
Section: 19mentioning
confidence: 97%
“…The pathology may be asymptomatic,[ 24 ] but can cause postural headaches due to a “cerebrospinal fluid sink” mechanism, as well as back pain, leg pain, or rectal pain. [ 25 21 ] If significant arachnoid cysts are present, the compression of lumbosacral nerve roots may lead to neurological deficits, including cauda equina syndrome (CES).…”
Section: Introductionmentioning
confidence: 99%